The value of print, the value of porn - Cardoso Daniel; Paasonen Susanna (Taylor & Francis, 2022)
As the distribution of pornography has shifted online, the markets of DVDs and print magazines have drastically shrunk. At the same time, a range of independent and artistic magazines on pornography and sexual cultures has appeared, operating primarily on paper. By focusing on Ménage à trois (Mà3), a Finnish queer-feminist porn magazine (est. 2012) and Phile, a Toronto-based magazine on ‘sexual curiosity’ (est. 2017), this article inquires after the affordances, appeal, and value of physical print artefacts in a cultural context dominated by the imperatives of digital affordances. Through interviews with editors and designers, we ask how these magazines position themselves vis-à-vis the denominator of pornography in the content they publish and in the uses that they see the magazines as entering. They make it possible to consider both the issue of regional and language-specific reach in independent publishing and the different value that the editorial teams associate with pornography.